Determinación de los valores de hematocrito y su incidencia en anemia en niños de 5 a 10 años ciudadela sol brisa cantón Babahoyo provincia los Ríos primer semestre 2015. - Sandoval Triguero, Marjorie Alexandra (2015)
The hematocrit is the percentage of total blood volume composed of red cells. The average values vary between 40.3 and 50.7% in men and between 36.1 and 44.3% in women, due to increased muscle and therefore more oxygen requirement of the first. These figures may change according to various physiological factors such as age and physical condition of the subject. It is an integral part of the count, along with the measurement of hemoglobin and white blood cell count and platelets. A low level of red blood cells causes anemia; There are numerous factors that can contribute to develop anemia, such as low iron intake; or patients with chronic kidney disease who do not produce enough erythropoietin to stimulate red blood cell production in the bone marrow. The increase in hematocrit indicates a polycythemia (increased number of red blood cells). Polycythemia may be primitive as in Vaquez disease, is a disease affecting bone marrow, where red blood cells are synthesized. The values of the red blood cells will be too high. It may also be high due to heart disease, tumors or increased synthesis of hormones that stimulate the production of red blood cells. In cases of polycythemia, blood is thicker and the main risk is the occurrence of thrombosis, blood clots that can block blood flow.